From almost to altogether : sermons on Christian discipleship - Wesley, John, 1703-1791 (Franklin, Tennessee : Seedbed Publishing, 2015)
John Wesley's phrase, "holiness of heart and life," summarizes his vision of Christian discipleship. When God's grace renews the heart inwardly, then the believer is transformed by living out a practical Christian life in the world. From Almost to Altogether is a collection of nine sermons addressing Wesley's teaching on Christian discipleship. Wesley believed that there is a real difference between the "almost Christian" and the "altogether Christian." The love of God is such that all are invited to receive that love and the transformation it brings. Collectively, these sermons show what it means to move from almost to altogether in the Christian life.
Introduction -- 1. The circumcision of the heart -- 2. The almost Christian -- 3. The first-fruits of the Spirit -- 4. The way to the Kingdom -- 5. Marks of the New Birth -- 6. On sin in believers -- 7. The repentance of believers -- 8. The good steward -- 9. The more excellent way.
Online resource; title from PDF title page (EBSCO, viewed May 31, 2016).
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Sermons, English -- Early works to 1800.; Christian life -- Sermons; Holiness -- Sermons; Christian life -- Methodist authors; Christian life; Christian life -- Methodist authors; Holiness; Sermons, English; RELIGION / Christian Theology / Soteriology; Early works; Sermons; Electronic books